SuperMind: a survey of the potential of superconducting electronics for neuromorphic computing. (1st May 2022) - Schneider, Michael; Toomey, Emily; Rowlands, Graham; Shainline, Jeff; Tschirhart, Paul; Segall, Ken
Abstract: Neuromorphic computing is a broad field that uses biological inspiration to address computing design. It is being pursued in many hardware technologies, both novel and conventional. We discuss the use of superconductive electronics for neuromorphic computing and why they are a compelling technology for the design of neuromorphic computing systems. One example is the natural spiking behavior of Josephson junctions and the ability to transmit short voltage spikes without the resistive capacitive time constants that typically hinder spike-based computing. We review the work that has been done on biologically inspired superconductive devices, circuits, and architectures and discuss the scaling potential of these demonstrations.